Penguatan Bacaan Al-Qur’an Hukum Idgham Bighunnah Dan Idgham Bilaghunnah Melalui Media Flashcard Di TPA Darussa’adah Palangka Raya - Sulistia Wati (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
This community service activity focuses on teaching students at TKA/TPA Darussa'adah Palangka Raya with a focus on using Flashcard media in learning Al-Qur'an activities. The purpose of this service is to see and explore the potential of using Flashcard media in the activity of strengthening Qur'anic recitation of idgham bighunnah and idgham bilaghunnah tajweed laws that can be useful and easy to understand for santri children. The service method used is Service Learning (SL) with two stages. The first stage, field analysis and program or activity project design. Second stage, the implementation of the service according to what has been designed. The results of the service show that the implementation of learning the Qur'an, especially the legal material of Idgham bighunnah and Idgham bilaghunnah through Flashcard media at TKA/TPA Darussa'adah, has proven to make it easier for children to understand the reading laws of Idgham bighunnah and Idgham bilaghunnah. This method of learning by utilizing interactive media also prevents children's boredom in learning the Qur'an.